Improved Temperature‐Dependent Ice Refractive Index Compilation in the Far‐Infrared Spectrum - Siheng Wang; Tong Ren; Ping Yang; Masanori Saito; Helen E. Brindley (Geophysical Research Letters)
Abstract A new ice refractive index compilation is reported for a broad spectrum ranging from 0.0443 to 106 μm, focusing on the pronounced temperature‐dependence of ice optical properties in the far‐infrared (far‐IR) segment (15–100 μm). A sensitivity study assuming spherical particles shows that selecting ice refractive indices at 12 temperatures and 215 wavelengths in the far‐IR region gives sufficient accuracy in interpolated refractive indices for developing a new ice crystal optical property database. Furthermore, we demonstrate the differences between the bulk single‐scattering properties computed for hexagonal ice particles with this new compilation compared to a previous iteration at three far‐IR wavelengths where substantial differences are noticed between the two ice refractive index compilations. We suggest that our new ice refractive index data set will improve downstream light‐scattering applications for upcoming far‐IR satellite missions and allow robust modeling of outgoing longwave radiation under ice cloud conditions.